Spatial angle dependent lasing from a dye-doped two-dimensional hexagonal photonic crystal made of holographic polymer-dispersed liquid crystals - Luo, D. (2013)
The observation of spatial angle dependent lasing from a dye-doped two-dimensional photonic crystal (2D PC) holographic polymer dispersed liquid crystals made of hexagonal lattice structure is reported. With the increasing output angle of the laser beam in the plane perpendicular to the 2D PC, the lasing wavelength is red-shifted. By analyzing the lasing oscillation trace, we found that the effective lattice constant changes with the output angle, causing the spatial angle dependent lasing.